O-72 Making decisions on behalf of people with dementia: how do proxies do it?. (1st September 2015) - Fetherstonhaugh, D; McAuliffe, L; Bauer, M; Shanley, C
Abstract : Background: The decision-making capacity of a person with dementia (PWD) has been shown to decrease as the severity of the dementia increases. Eventually, the PWD will reach a stage where they are no longer able to makedecisions for themselves. At this point, major decisions (e.g., moving intoresidential care, being transferred to hospital from residential care, consenting to an operation, and deciding on end-of-life care) become theresponsibility of someone else, typically a family member or a legallyappointed proxy. Aim: To explore how proxy decision-makers makedecisions on behalf of a PWD; and to explore whether they feel they needsupport in making these decisions, and if so, what types of support and meansof support delivery are preferred. Methods: The study was informed by Grounded Theory Methodology. 34 semi-structured interviews were undertaken with proxy decision-makers of a PWD (either legally appointed or else recognised as the 'person responsible') who had already made a major life decision on behalf of the PWD. Results: A mix of proxy decision-making methods was reported, and included both the substituted judgement standard and the best intereststandard, which were applied to a range of situations in which a major decisionhad been required. Discussion/Conclusion: Proxy decision-makers use a variety of ways tomake decisions on behalf of a PWD, most often in the absence of an advance caredirective. There is a need for greater support to assist proxy decision-makers throughwhat is often a complex and confronting process.